Axiological culture as a fundamental goal of modern education - Matviichuk, Andrii; Pelekh, Yurii (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
The relevance of the chosen topic is determined by the necessity of enhancing the role of education amidst growing geopolitical and socio-cultural tensions, as well as due to the tendency of excessive utilitarianization of education, which negates its culture-creating function. The objective of the study is the theoretical substantiation of the expediency of defining the formation of axiological culture as a fundamental goal of modern education. The paper conceptualizes the notion of “axiological culture” as a personality quality that includes the capacity for value reflection and modeling of value-balanced life strategies. The research substantiates the necessity of implementing the ideas of axiopedagogy and innovative educational methodologies for the practical realization of the task of forming axiological culture, particularly through the development of value intelligence. The conducted study proves that the formation of humanistic axiological culture through the development of value intelligence is the super-task of modern education, as it ensures social competence in the context of globalization challenges and dynamic socio-cultural changes.

Znaczenie wybranego tematu wynika z konieczności wzmocnienia roli edukacji w obliczu narastających napięć geopolitycznych i społeczno-kulturowych, a także z tendencji do nadmiernej utylitaryzacji edukacji, która neguje jej funkcję kulturalną. Celem badania jest teoretyczne uzasadnienie potrzeby kształtowania kultury aksjologicznej jako fundamentu współczesnej edukacji. W artykule pojęcie „kultura aksjologiczna” zostało ujęte jako cecha osobowości obejmująca zdolność do refleksji nad wartościami i modelowania zrównoważonych pod względem wartości strategii życiowych. Badania potwierdzają konieczność wdrożenia idei aksjopedagogiki i innowacyjnychmetodologii edukacyjnych w celu praktycznej realizacji zadania kształtowania kultury aksjologicznej, w szczególności poprzez rozwój inteligencji wartościowej. Przeprowadzone badania dowodzą, że kształtowanie humanistycznej kultury aksjologicznej poprzez rozwój inteligencji wartościowej stanowi priorytet współczesnej edukacji, ponieważ zapewnia rozwijanie kompetencji społecznych, istotnych w obliczu wyzwań globalizacji i dynamicznych zmian społeczno-kulturowych.
Kultura aksjologiczna jako fundamentalny cel współczesnej edukacji
Keywords: axiological culture; value intelligence; axiopedagogy; education; humanistic values; kultura aksjologiczna; inteligencja wartościowa; aksjopedagogika; edukacja; wartości humanistyczne